2000
DOI: 10.1034/j.1398-9995.2000.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Different airway responsiveness profiles in atopic asthma, nonatopic asthma, and Sjögren's syndrome

Abstract: The results of this study suggest that patients with asthma and subjects with Sjögren's syndrome display different bronchial responsiveness profiles for different challenge agents. Atopic subjects with asthma are more hyperresponsive to AMP than nonatopic subjects and patients with Sjögren's syndrome. More than one challenge may be required to detect different aspects of bronchial responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 25 publications
3
45
0
1
Order By: Relevance
“…The fact that both early and late asthmatic responses are sensitive to pharmacologic agents that block FcεRI-dependent MC activation implies a pathway by which MCs can potentiate AHR (17). Of note, however, is that AHR can exist as an isolated phenotype in nonasthmatic individuals, can precede the clinical onset of asthma, and is also present in nonatopic asthmatics (18). The question of whether MCs play a role in asthma independent of IgE and sensitization to allergen remains largely unexplored.…”
mentioning
confidence: 99%
“…The fact that both early and late asthmatic responses are sensitive to pharmacologic agents that block FcεRI-dependent MC activation implies a pathway by which MCs can potentiate AHR (17). Of note, however, is that AHR can exist as an isolated phenotype in nonasthmatic individuals, can precede the clinical onset of asthma, and is also present in nonatopic asthmatics (18). The question of whether MCs play a role in asthma independent of IgE and sensitization to allergen remains largely unexplored.…”
mentioning
confidence: 99%
“…Mechanisms underlying bronchial hyperresponsiveness in patients with primary Sjö gren's syndrome probably differ from those in asthmatic patients [65], but remain unknown. Chronic sputum production and recurring sinusitis are associated with severe chronic bronchiolitis in primary Sjö gren's syndrome [66].…”
Section: Connective Tissue Diseasesmentioning
confidence: 98%
“…Although systemic steroids have been proposed by some authors, it does not appear efficacious in most cases [51]. Low-dose macrolides have been proposed in subjects with bronchiolitis related to rheumatoid arthritis [41] and may be proposed in Sjö gren's syndrome [65]. Inhaled steroids and long-acting bronchodilators could be proposed in patients with bronchial hyperresponsiveness, although one study suggested that this approach is not very effective in Sjö gren's syndrome [71].…”
Section: Connective Tissue Diseasesmentioning
confidence: 99%
“…Unlike asthma, eosinophils do not seem to act on hyperresponsiveness in Sjögren's syndrome. The intensity of hyperresponsiveness is not correlated with salivary gland infiltration [69] or with exhaled nitric oxide level [71]. No difference in bronchial gland atrophy was observed between Sjögren's syndrome patients and controls [72].…”
Section: Bronchial Hyperresponsivenessmentioning
confidence: 99%